2008
DOI: 10.1248/bpb.31.1096
|View full text |Cite
|
Sign up to set email alerts
|

BCH, an Inhibitor of System L Amino Acid Transporters, Induces Apoptosis in Cancer Cells

Abstract: Amino acids are essential to support protein synthesis, which is required for cell growth and proliferation. Amino acid uptake into the cell is mediated by amino acid transporters located on the plasma membrane. 1,2)The system L amino acid transporters are an amino acid transport system that transports neutral amino acids, including several essential amino acids, in a Na ϩ -independent manner.1,3) It is a major route for providing living cells, including cancer cells, with amino acids. 1,3)We isolated LAT1 (L-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

7
124
0

Year Published

2009
2009
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 117 publications
(131 citation statements)
references
References 30 publications
7
124
0
Order By: Relevance
“…Although inhibition of LAT1 affects cell proliferation (47,48), its genetic or chemical ablation results in mTOR inhibition and impaired cell growth (27, 28, 48 -50). Our data indicate that Ͼ90% of L-isoleucine uptake is lost when CD98hc is absent.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Although inhibition of LAT1 affects cell proliferation (47,48), its genetic or chemical ablation results in mTOR inhibition and impaired cell growth (27, 28, 48 -50). Our data indicate that Ͼ90% of L-isoleucine uptake is lost when CD98hc is absent.…”
Section: Discussionmentioning
confidence: 99%
“…By expressing such transporters coupled with extracellular matrix receptors, cells can control AA adequacy, reactive oxygen species impact, and anchoring/migration, leading to sustain cell proliferation, critical for tumor cells (54). To date, many studies have focused on the search for either transporter (xCT, LAT1) inhibitors or integrin antagonists as anti-cancer strategies (47,48,55,56). Even though these molecules are appealing targets, encouraging, yet limited results, have been obtained so far.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, L-type amino-acid transporter 1 (LAT1) is highly expressed in malignant tumours to support growth and proliferation, and the inhibition of LAT1 activity led to cancer cell apoptosis (Kim et al, 2008).…”
mentioning
confidence: 99%
“…Several comparative studies have shown that amino acidbased tracers have better performance than 18 F-FDG in brain tumor diagnosis [2][3][4]. Whereas 18 F-FDG uptake is generally a measure of glucose metabolism, amino acid-based PET can provide information on amino acid metabolism and the function of various amino acid transporters. Currently, amino acidbased PET scans are often performed in the clinic when a brain tumor is diagnosed by either magnetic resonance imaging (MRI) or computed tomography (CT), which can aid in personalized treatment planning.…”
mentioning
confidence: 99%
“…However, widespread clinical application of possible due to the short half-life of 11 C (20.38 min) and low efficiency in radiolabeling (radiochemical yield usually <5%). The use of 18 F to label methionine, without interfering with its biological activity, may solve this problem due to the longer half-life of 18 F (109.7 min) and its wide availability at the majority of PET centers. However, direct labeling of methionine with 18 F is very challenging, since even minor modification of the side chain will significantly alter the biological properties of the resulting methionine analog.…”
mentioning
confidence: 99%